2021
DOI: 10.3389/fgene.2021.771435
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing Genes by Using Text-Mined Co-Occurrence Features for Cancer Gene Panel Discovery

Abstract: Developing a biomedical-explainable and validatable text mining pipeline can help in cancer gene panel discovery. We create a pipeline that can contextualize genes by using text-mined co-occurrence features. We apply Biomedical Natural Language Processing (BioNLP) techniques for literature mining in the cancer gene panel. A literature-derived 4,679 × 4,630 gene term-feature matrix was built. The EGFR L858R and T790M, and BRAF V600E genetic variants are important mutation term features in text mining and are fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…B Schematic diagram modified from Ref. [ 168 ]. A gene panel analysis framework was developed that can discover gene panel characteristics based on BioNLP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B Schematic diagram modified from Ref. [ 168 ]. A gene panel analysis framework was developed that can discover gene panel characteristics based on BioNLP.…”
Section: Discussionmentioning
confidence: 99%
“…In the different machine learning models, the peak accuracies for the prediction of MSK-IMPACT and OCP were 0.959 and 0.989, respectively. Receiver operating characteristic curve analysis also confirmed that the neural network model had better predictive performance (AUROC = 0.992) [ 168 ]. By using text-mined post-occurrence features, the literature for each gene can be ascertained, and this approach could be used to evaluate several existing gene panels and predict the remaining genes using a portion of the gene panel set, leading to cancer detection.…”
Section: Ai-based Medical Article Retrievalmentioning
confidence: 91%
See 1 more Smart Citation
“…However, we could not explain the biological significance of the vector in the neural-embedding model. Table 4 [ 69 , 70 , 71 , 72 , 73 , 74 ] shows that various data-mining techniques have been used to classify gene-mutation diseases.…”
Section: Text Mining For Identifying Genes Targets In Cancersmentioning
confidence: 99%
“…Our own work contextualized the genes for clinical precision medicine, presenting druggable targets, hereditary cancer syndrome mutations, and illness subgroups [ 74 ]. The hypergeometric test was used to construct the mutational landscape of the actionable cancer genome from the biomedical literature, which was then confirmed using the NGS database.…”
Section: Text Mining For Identifying Genes Targets In Cancersmentioning
confidence: 99%